Harmonic distortion in public low-voltage grids Comparison of the situation in Colombia and Germany (2015)
Current and voltage harmonic levels in LV grids depend not only on the harmonic emission of non-linear loads, but also on the characteristics of the grid and the voltage distortion of the upstream grid. Based on several measurements, it was found that Colombia and Germany have considerable differences in the current harmonic emission of electronic devices and voltage distortion in the LV-grids. These differences are the result of different regulation methodologies and the characteristics of the grid. Detail measurement campaigns are needed in both countries in order to verify the voltage and current harmonic levels, and to analyze the network efficiency and hosting capacity in terms of harmonics.